Study on the Vibration Effect of Short Footage Blasting Load on Surrounding Rock-Support Structure of Tunnel - Chunquan Dai; Hongtao Sui; Chao Ma (Shock and Vibration)
In the excavation process of a drilling and blasting tunnel, it takes multiple blasting excavations to form, so it is inevitable to produce multiple blasting impact loads, which will cause certain vibration damage to the surrounding rock-support structure. To solve this problem, based on the attenuation formula of blasting vibration wave and considering the cumulative effect of short footage blasting load, the radial displacement formula of surrounding rock particles is derived, and the analytical solution of vibration velocity field is obtained by using the method of separating variables. Then, taking Cuobuling station of Qingdao Metro as the engineering background, the finite element software is used to simulate the tunnel excavation process under the action of short footage multiple blasting. The vibration damage impact of multiple blasting loads on the surrounding rock-supporting structure is analyzed from the accumulated displacement value and vibration velocity cumulative value of the excavation tunnel. The results show that the damage accumulation effect is produced in the surrounding rock of each section during the blasting construction, among which the accumulation is the largest at the arch bottom. With the increase of blasting times, the damage of the surrounding rock is still accumulating gradually. Compared with the first blasting, the peak value of vibration velocity of the second blasting increased by 114%, and with the increase of blasting times, the variation trend of maximum vibration velocity of the measuring point showed an upward trend, but the subsequent vibration acceleration decreased. Under the condition of grade V surrounding rock, when the thickness of the concrete spray layer is 350 mm, the maximum displacement cumulative value of each measuring point in profile 1-1 is reduced by about 50.4% compared with that without support. According to the displacement nephogram of the concrete spray layer, the displacement of the concrete spray layer accumulates after three times of blasting, which affects the stability of the supporting structure. Finally, an example analysis is carried out and compared with the analytical model results to verify the accuracy of the mechanical model.